Gastro Destination of Banjarmasin City through James William Carey's Ritual Communication Model - Firda Dewi Irawan; Bambang Dwi Prasetyo (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
In creating the branding of a city, indirectly through a communication process which from a cultural perspective involves ritual communication. Currently, the branding Banjarmasin is the city of a thousand rivers. The correlation between the river and Soto Banjar triggered the discovery of the concept of gastro branding and gastro destination. This research aims to increase awareness and solve how the idea of a gastro destination can be used appropriately and well in Banjarmasin City. This study adopts the thinking of the Chicago School and uses the action research method. The results of this study are Soto Banjar as a typical culinary, and the river as an Icon of the City of Banjarmasin becomes an irreplaceable element in representing the identity and residents of the City of Banjarmasin. This relates to how the ritual communication process can form a common belief and eventually become a potential within the scope of Gastro Destination. Furthermore, gastro destinations can overcome problems in the field related to the preservation of river cultural life in the city of Banjarmasin. This is related to strengthening the town's identity, where the orientation of the community begins to change to land and maintaining the existence of Soto Banjar as a typical culinary during competition with foreign culinary. Further research can sharpen the correlation between history and culture and provide strength for social life to survive from time to time.